Acquired haemophilia A in the postpartum and risk of relapse in subsequent pregnancies: A systematic literature review. Issue 2 (6th February 2021) - Dewarrat, Natacha; Gavillet, Mathilde; Angelillo‐Scherrer, Anne; Naveiras, Olaia; Grandoni, Francesco; Tsakiris, Dimitrios A.; Alberio, Lorenzo; Blum, Sabine
Abstract: Background: About 1%–5% of acquired haemophilia A cases affect mothers in the postpartum setting. Aims: This study delineates the characteristics of this disease, specific to the postpartum setting, notably relapse in subsequent pregnancies. Methods: Report of two cases and literature study (1946–2019), yielding 73 articles describing 174 cases (total 176 cases). Results: Patients were aged 29.9 years (17–41) and 69% primigravidae . Diagnosis was made at a median of 60 days after delivery (range 0–308). Bleeding types were obstetrical (43.4%), cutaneous (41.3%), and muscular (36.7%). In >90% of the cases, FVIII at diagnosis was <1% (range 0%–8%). FVIII inhibitor was documented in 75.4% cases (median titre of 20 BU/ml, range 1–621). Haemostatic treatment was necessary in 57.1% using fresh frozen plasma (16%), factor concentrate (27.6%) and/or bypassing agents (37.4%). Immunosuppressive treatment was administered in 90.8%, mostly steroids (85.3%), alone or combined with immunosuppressants (27%). Rituximab was used mostly as a second line treatment. Only 24 patients (13.6%) had documented subsequent pregnancies and 6 (22.2%) suffered haemophilia recurrence during pregnancy. Conclusion: This study allows better definition of: (1) clinical and laboratory characteristics of postpartum acquired haemophilia, (2) response to therapy, and (3) the risk of relapse for subsequent pregnancies.